단어 연상을 통한 언어장애아동의 연상어 반응 유형 및 품사 유형 분석 - 박선희(Sun Hee Park) (언어치료연구, 2016)
목적: 단어 연상을 통하여 언어장애아동의 연상어 반응 유형을 살펴보고, 이를 일반아동과 비교하고자 하였다. 자극어에 대한 언어장애아동의 연상어 반응 유형과 연상어 품사를 분석하여 이를 통한 언어장애아동의 효과적인 어휘 지도방법을 모색하고자 함에 연구의 목적을 둔다. 방법: 연구대상은 언어장애아동 20명, 언어장애아동과 언어연령을 일치시킨 일반아동 20명, 전체 40명을 선정하였다. 연구도구인 자극어는 명사 10개, 형용사 5개, 동사 5개로 제시하였다. 자료분석을 위하여 연상어 반응 유형은 형식, 의미, 화용으로 구분하였고, 형식은 다시 형태, 수식, 서술로 그리고 의미는 유의, 반의, 동위, 상위, 하위, 상징으로 세분화하여 살펴보았다. 연상어의 품사는 명사, 동사, 형용사, 부사, 기타로 구분하여 분석하였다. 연상어 반응 유형 분석과 연상어 품사 분석에서는 연상어 평균과 백분율을, 두 집단의 차이를 비교하기 위하여 t-검증을 실시하였다. 결과: 첫째, 언어장애아동은 형식 반응 유형에서 일반아동은 의미 반응 유형에서 연상어 산출이 많았고, 두 영역에서는 통계적으로 유의한 차이를 보였다. 형식에서 언어장애아동은 수식이, 일반아동은 서술에서 연상어를 높게 산출하였다. 의미에서 언어장애아동은 하위, 유의, 동위, 반의, 상징의 순서로, 일반아동은 하위, 동위, 유의, 반의, 상징, 상위의 순서로 연상어를 산출하였다. 둘째, 연상어 품사 유형 비교에서 언어장애아동과 일반아동은 모두 명사, 형용사, 동사, 부사의 순서로 연상어를 산출하였고, 명사에서 통계적으로 유의한 차이를 보였다. 결론: 언어장애아동은 형식 연상 중심의 결합적 연상을, 일반아동은 의미 중심의 계열적 연상을 많이 산출하였다. 이로써 언어장애아동은 주제적이고, 배열 중심의 연상이 강함을 알 수 있었다. 또한 언어장애아동은 명사 연상어의 산출이 일반아동에 비하여 많았다. 따라서 언어장애아동의 연상 반응을 기초한 어휘 지도 전략을 마련해야 할 것으로 기대한다. Purpose: The purpose of this study was to investigate response words through word association between children with language impairments and normal children. Response words were analyzed to find appropriate stimuli words for the children with language impairment in order to seek effective vocabulary instruction methods for children with language impairments. Methods: Twenty children with language impairments and 20 age-matched normal children participated in this study. Twenty stimuli words were selected based on word frequency, accessibility, and understanding and an investigation was constructed from the literature review. The stimuli words were comprised of ten nouns, five adjectives, and five verbs. Response word types were classified by form, meaning, and pragmatics for the data analysis. Form-based associations were classified by morphology, modification, description, and meaning-based associations were classified by synonym, antonym, coordinate, hypernym, hyponym, and symbolic. Response word of word class were analyzed separately as noun, verb, adjective, adverb, and the like. In the analysis of response words response type and in the analysis of the percentage and word class response words mean, the difference between the two groups was use to compare t-verification. Results: First, form and meaning were significantly different between the children with language impairment and normal children. Children with language impairment expressed form-based association more compared to normal children. Second, noun use was significantly different between the children with language impairments and normal children. The children with language impairment expressed noun association more compared to normal children. KCI Citation Count: 2